Hugo Chávez dan Kebangkitan Populisme-Kiri Amerika Latin: Venezuela Era Hugo Chávez (1998-2006) - Daniel Hutagalung (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2014)
Hugo Chávez appeared and emerged in Venezuela under political-economic crisis. This article argues that his power struggle supported by the people because Chavez vision and mission are to favour the people inrerest, and he takes care about people. . Chave political project, as stated Ellner as non- revolutionary path of radical populism, expressed through various political program missions, namely to encourage social revolutionary program, but not in the political project of the revolution, at least during the Chávez powers throughout 1998-2006. However, Ellner mentioned that non- revolutionary path of radical populism can also lead to revolutionary-path, meaning that political poryek Chávez is still unfinished and still possible to reach a variety of changes, whether the "Bolivarian Revolution" will take the form of non-revolutionary transformation, or even revolutionary- path.